Features Of The Electrical Power Supply Course In Forming Energy-Related Competencies In Students And Analysis Of Foreign Experience - Alikulova , Saodat (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
In the process of teaching electrical engineering in higher education institutions, a systematic approach, clear goal setting, consideration of students' behavior, and the formation of knowledge, skills, and competencies in them based on a technological approach are considered a continuous process of education that allows achieving the desired results.